Readability of Literature Supplied with Plant Protection Chemicals - Jirli, Basavaprabhu; Jiyawan, Ram; Kumar, Amit; Sharada, (Indian Journal of Extension Education, 2013)
Printed materials have been accepted world wide as an important means of communication and have greater significance  in the context of increased literacy level over the last few decades. The effectiveness of these printed materials depends  largely on the extent to which they are readable. The present study was undertaken to analyze the readability of literature  supplied along with plant protection chemicals. The study was conducted in Sevapuri block of Varanasi district of Uttar  Pradesh, because this block has high literacy percentage in comparison to other blocks. Four villages under this block  namely Maharajpur, Gaharpur, Jaddupur and Bhelupur were selected randomly for the study. A total of 110 farmers who  grew varieties of cereals and vegetables and used Plant Protection Chemicals (PPCs) for protecting their crops from the  incidence of insect-pests and diseases were the respondents of the study. The findings of the study revealed that majority  of the farmers had completed their higher secondary education (61%). Further all the farmers said that they were aware  about literature supplied with PPCs, but only 37 per cent of them read the literature. All the farmers agreed that too many  technical words used, font size used, poor paper quality, lack of illustration and difficult to understand the application  methods regarding PPCs suggested in the literature considered as main constraints in reading the literature. Hence  readability constraints should be eliminated and farmers should be encouraged to read and follow the instructions  mentioned in the literature.
Keywords: Readability; awareness; farmers; plant protection chemicals (PPCs); constraints